-72+4y+6y=-6

Simple and best practice solution for -72+4y+6y=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -72+4y+6y=-6 equation:


Simplifying
-72 + 4y + 6y = -6

Combine like terms: 4y + 6y = 10y
-72 + 10y = -6

Solving
-72 + 10y = -6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '72' to each side of the equation.
-72 + 72 + 10y = -6 + 72

Combine like terms: -72 + 72 = 0
0 + 10y = -6 + 72
10y = -6 + 72

Combine like terms: -6 + 72 = 66
10y = 66

Divide each side by '10'.
y = 6.6

Simplifying
y = 6.6

See similar equations:

| f(x)=5cosx+8 | | ln(2x-5)=2 | | 276/8=203/4+v | | x^2+3.5x=7 | | 6/17=-54/x | | (1+v)(3v-2)=0 | | 5t-6=3-4t | | -9(-9)-7y=63 | | 5x-9=35(x-2) | | -3(1-x)=2(x+1) | | 8-x=x-1 | | -9(1)-7y=63 | | x^2-5.5x-.5=0 | | -9*(1)-7y=63 | | x^2-7x+6=(x-1)(ax+b) | | a(n)=3+2(n-1) | | x^2-11/2x-1/2=0 | | 2(x-1)=-3(x+3) | | (3x-2)3=0 | | 17x-27=30x-94 | | 3y=2x+65x=y+20 | | 8y^2-10y-63=0 | | 2y-2=4x | | 8y-2x(y+7)-y=0 | | 3(x+2)=y-b | | s^2-21s+108=0 | | x^3+5x^2+3x-9=(x+3)(ax^2+bx+c) | | y+5=2(x+4) | | x^3+5x^2+3c-9=(x+3)(ax^2+bx+c) | | -x=4x-2 | | 12x9/3x4 | | -2x=4x-2 |

Equations solver categories